2016
DOI: 10.1120/jacmp.v17i1.5452
|View full text |Cite
|
Sign up to set email alerts
|

On the sensitivity of TG‐119 and IROC credentialing to TPS commissioning errors

Abstract: We investigate the sensitivity of IMRT commissioning using the TG‐119 C‐shape phantom and credentialing with the IROC head and neck phantom to treatment planning system commissioning errors. We introduced errors into the various aspects of the commissioning process for a 6X photon energy modeled using the analytical anisotropic algorithm within a commercial treatment planning system. Errors were implemented into the various components of the dose calculation algorithm including primary photons, secondary photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Of these, dosimetric errors (i.e., outside the 3% calibration or 2% relative dosimetry tolerances) are often the most concerning because of their direct impact on patient care, i.e., dose delivery. While a given clinical treatment plan may or may not be substantially impacted by a specific error in an individual basic dosimetry parameter, basic dosimetric errors such as those evaluated in the current study have been shown to routinely manifest as problems in clinical plans [14,15]. Moreover, good dosimetric agreement should be achievable overall for this test suite because the test suite includes only relatively simple conditions: only square fields, no extremely large or small fields, and no superficial or extremely deep locations.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, dosimetric errors (i.e., outside the 3% calibration or 2% relative dosimetry tolerances) are often the most concerning because of their direct impact on patient care, i.e., dose delivery. While a given clinical treatment plan may or may not be substantially impacted by a specific error in an individual basic dosimetry parameter, basic dosimetric errors such as those evaluated in the current study have been shown to routinely manifest as problems in clinical plans [14,15]. Moreover, good dosimetric agreement should be achievable overall for this test suite because the test suite includes only relatively simple conditions: only square fields, no extremely large or small fields, and no superficial or extremely deep locations.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] This result was also simulated in work by McVicker et al, where gamma analyses comparing plans calculated with and without commissioning errors could not reveal clinically severe effects, even with stringent 2%/2 mm criteria. 3 These data suggest that film dosimetry may have limited applicability in error detection for IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, a substantial number of institutions still fail to meet the minimum criteria, thus warranting further investigation to determine the root cause. Previous works like that of McVicker et al 3 have used the H&N phantom to determine the detectability of potential commissioning errors. While this work exposes some of the limitations of the phantom, it does not address the prevalence and detection of errors in multi-institutional performance.…”
Section: Introductionmentioning
confidence: 99%
“…[1417] In this work, small ionization chamber (Pinpoint) was used instead of larger ionization chamber (Farmer) which was used by other researchers. [141516] The main advantage of this small chamber is its use for increasing the accuracy, in particular, in high-dose gradient and edge of the fields. [18]…”
Section: Discussionmentioning
confidence: 99%
“…[567] Recently, researchers have done TG-119 protocol on different planning systems, different detectors, and LINAC machines with different photon energies and obtained different gamma criteria. [8910111213141516]…”
Section: Introductionmentioning
confidence: 99%